Kebijakan Produk Standarisasi International - Radiyyah, Afif Fathanah; Manurung, Nabila Tasya Nurhafifah; Hasibuan, Sovy Muti Ardianty; Suhairi, Suhairi (Jurnal Informatika, 2024)
International product standardization policies are related to the dynamics of global trade and the complexity of the current global market. In an ever-evolving and globally connected environment, harmonization of product standards is important to facilitate the more efficient flow of goods and services across borders. Differences in national standards between countries can be a major obstacle in international trade. Therefore, a uniform and compatible standardization policy throughout the world is essential to create a fair and open trading environment for all market participants. This research aims to determine the use of standardization in Indonesia and what benefits are obtained from implementing product standardization policies.